Valorization of Empty Palm Oil Fruit Bunch Fiber as Hydrophobic Cement Board - Halim, Abdul; Frizky Septian Pramasta; Wulandari Kusuma Dewi; Janis Wardila Ningsih; Ferian Erlangga; Roni Maryana; Eka Lutfi Septiani (Jurnal Bahan Alam Terbarukan, 2024)
The penetration of property business and technology has increased significantly increased due to economic improvement. One of the materials in high demand is cement board. Cement board compost of agricultural waste limits its application due to its easily absorbing water. Herein, we used the empty palm oil fruit bunch as a filler in cement board and coated it with polystyrene from styrofoam waste. The board shows good mechanical strength and fulfill the minimum requirement for cement board standard of Indonesian National Standard (SNI). The board also shows hydrophobic properties, and no water droplets permeate the surface even after 4 h. These findings open a new application for cement board not only for the interior but also for the exterior.